ANALYSIS OF THE LEVEL EROSION HAZARD ON LAND USE CHANGE IN THE TENGGULUN HULU SUB-WATERSHED, ACEH TAMIANG DISTRICT - Ardhika Bestary Rizkiani; Ratna Wilis (GeoEco, 2025)
The objectives of this paper are 1) to determine the level of erosion hazard in 2003, 2013 and 2023 in the Hulu Watershed of Tenggulun District, Aceh Tamiang Regency, 2) to determine the level of erosion hazard in the future, namely in 2033, 3) and to know the Erosion Disaster Policy Direction in the Hulu Watershed of Tenggulun District, Aceh Tamiang Regency. The method used is a mixed methods, namely survey research and spatial data analysis. Furthermore, in processing the direction of disaster mitigation policies, the Analytical Hierarchy Process method is carried out, which aims to formulate the priority of appropriate directions for erosion disaster mitigation. Based on the study's results, the level of erosion hazard using the USLE method in 10 years has significantly changed in 2003, 2013, and 2023. Severe erosion events are found in Selamat Village and Tenggulun Village. Furthermore, the prediction of the level of erosion hazard using the mollusce plugin method, to be able to see the simulation of future changes, and can see the kappa value index with a value of 6-8 which means the results of the value are very good within the scope of the kappa index assessment. Therefore, it can be used in the future. In addition to a policy analysis of erosion disaster mitigation policy direction, three criteria were obtained: the environment, erosion disaster mitigation, and policy. Subcriteria that are prioritised include the existence of sustainable watershed management.